Auditoría financiera como herramienta estratégica para la prevención de riesgos y detección de fraudes en la empresa comercializadora de repuestos automotriz SURTICARS S.A.S en el año 2023 del mercado público de santa marta - Plaza Bolaño Teresa Yulieth; Rozo Montero Adriana Carolina (Universidad Antonio Nariño, 2025)
This project entitled financial audit as a strategic tool for risk prevention and fraud detection in the automotive spare parts marketing company Surticars SAS in the year 2023 of the public market of Santa Marta, addresses the evaluation of the administrative and operational procedures in Surticars S.A.S, a family business in the commercial sector in Santa Marta, focusing on its vulnerability to fraud and the need to implement adequate controls. Its main objective is to analyze the financial audit as a strategic tool for risk prevention and fraud detection in the automotive spare parts marketing company Surticars SAS in the year 2023 of the public market of Santa Marta, using a qualitative approach that included interviews to better understand the operation of the business and its possible exposure to irregular situations. In Surticars SAS, control problems in management, lack of rules of conduct and errors in the hiring of personnel were detected. Therefore, it is suggested to implement strategies to prevent and detect fraud to improve your processes, protect your operations and guarantee your permanence in the market.